IoT Games and Gamified Systems: Summertime Sadness or Lust for Hype? - Carneiro, Nayana; Nunes, Caio; Raulino, Natã; Gomes, Igor; Andrade, Rossana; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
The Internet of Things (IoT) has gained much space in people's everyday lives in the last few years, and it is already possible to see IoT applications widely used in various domains, such as healthcare and industry. The convergence of IoT and digital games also creates opportunities for HCI & Digital Games research, supposedly opening countless possibilities for innovative games and challenging research. However, research on this topic appears to suffer from a generalized lack of clarity in its basics. Following this thread, we conducted a systematic mapping study and analyzed 22 papers that proposed or evaluated IoT games and gamified systems (IoTGGS), aiming to identify characteristics, patterns, and research opportunities related to HCI design and evaluation. However, our own frustrations in this endeavor also led us to identify shortcomings in commonly-used approaches. Thus, this paper contributes to the debate not only by focusing on the convergence between games and IoT with a systematic approach but also discussing the apparently dead-end we have found when closely analyzing this research topic. We present a brief panorama of the field and the identified gaps and raise possible new directions that could help take IoTGGS research to the next level.